OPTIMALISASI KINERJA DIMODERASI STRATEGI GREEN MARKETING PADA UKM - Yuliana, Ika; Lady Faerrosa; Maghfira Rizky Maulani; Susilo Talidobel; M. Chothibul Umam Assa’ady (Universitas Mbojo Bima - Nusa Tenggara Barat, 2023)
The increasing number of SMEs will always be related to sustainability, and the urgency to care for the environment is becoming increasingly high so conventional marketing is starting to shift towards green marketing. Even though they have a large role in economic development, regarding sustainability issues, SMEs have not contributed optimally. The sampling technique is based on the principle of non-probability sampling. Questionnaires were processed by 108 culinary UKM owners in Lombok, using Structural Equation Modeling (SEM). The results of testing the direct influence of entrepreneurial orientation on optimizing the performance of SMEs in Lombok show that there is an insignificant influence. Green marketing has a moderating effect on entrepreneurial orientation and optimizing the performance of SMEs in Lombok. Keywords: Entrepreneurial Orientation, Green marketing, Performance of SMEs